Fairness aspects in personnel scheduling - Lena Antonia Wolbeck (Freie Universität Berlin, School of Business & Economics, 2019)
In industries like health care, public transport or call centers a shift-based system ensures permanent availability of employees for covering needed services. The resource allocation problem - assigning employees to shifts - is known as personnel scheduling in literature and often aims at minimizing staffing costs. Working in shifts, though, impacts employees' private lives which adds to the problem of increasing staff shortage in recent years. Therefore, more and more effort is spent on incorporating fairness into scheduling approaches in order to increase employees' satisfaction. This paper presents a literature review of approaches for personnel scheduling considering fairness aspects. Since fairness is not a quantitative objective, but can be evaluated from different point of views, a large number of fairness measurements exists in the literature. Furthermore, perspective (group vs individual fairness) or time horizon (short-term vs long-term fairness) are often considered very differently. To conclude, we show that a uniform definition and approach for considering fairness in personnel scheduling is challenging and point out gaps for future research.
urn:nbn:de:kobv:188-refubium-26290-5
Keywords: 330; Long-Term Fairness; Preference Scheduling; Optimization; Literature Review